Performance indicators of teams at the 2003 World Handball Championships for women in Croatia - Ohnjec, K.; Vuleta, D.; Milanovic, D.; Gruic, I. (Kinesiology, 2008)
The research was conducted on a sample of 60 handball matches (a total of 120 play records of individual teams) during the preliminary part of the 2003 World Championship for women in Croatia. Twentyfour different female national handball teams were divided into four preliminary competition groups of six teams. The goal was to determine and analyse the factors of performance or situational efficiency in handball. The research focused on the differences in variances of the situational factors among the teams and on the contribution of standard situational parameters to the criterion outcomes of handball matches defined as the goal-difference in the match`s final score. The sample of predictor variables encompassed the shooting efficiency parameters across playing positions, assists, 7-m-throws won, and technical errors committed. The criterion variable was defined as the goal-difference of the match`s final score. Multivariate analyses of variance were used to determine the differences that were statistically significant at the level of p<.01 among the variances of the observed standard parameters of performance. Therefore, each preliminary group was observed separately. The series of regression analyses was used to define the contribution of the predictor variables to the performance of the teams. The obtained results showed that the performance of the teams in each group was described by different performance factors; the statistical significance was determined in all the groups at a high conclusion level (p<.01). The conclusion was that the final competition efficacy model or performance of the teams in every preliminary group or at the end of the competition was preconditioned by different factors.